Open and nimble : finding stable growth in small economies. - Lederman, Daniel, 1968-; Lesniak, Justin T. (Directions in development (Washington, D.C.). Countries and regions., 2018)
Does economic size matter for economic development outcomes? If so are current policies adequately addressing the role of size in the development process? Using working age population as a proxy for country size, this publication systematically analyzes what makes small economies unique. Small economies are not necessarily prone to underdevelopment and in fact can achieve very high income levels. Small economies, however, do tend to be highly open to both international trade and foreign direct investment, have highly specialized export structures, and have large government expenditures relative to their Gross Domestic Product. The export structures of small economies are concentrated in a few products or services and in a small number of export destinations. In turn, this export concentration is associated with terms of trade volatility, which combined with high exposure to international trade, implies that small economies tend to face more volatility on average as external volatility permeates national economic life. Yet small economies tend to compensate for their export concentration by being nimble in the sense of being able to change their production and export structure relatively quickly over time. Moreover, limited territory plays a role in shaping how economies are affected by natural disasters, even when the probability of facing such disasters is not necessarily higher among small than among large economies. The combination of large governments with macroeconomic volatility seems to be associated with low national savings rates in small economies. This combination could be a challenge for long-term growth if productivity growth and foreign investment do not compensate for low domestic savings. The book finishes with some thoughts on how policy makers can respond to these issues through coordinated investments and regional integration efforts, as well as fiscal policy reforms aimed at both increasing public savings and conducting countercyclical fiscal policies.